Uncertainty increases curiosity, but decreases happiness - Lieke L. F. van Lieshout (Nature Portfolio, 2021)
Abstract You probably know what kind of things you are curious about, but can you also explain what it feels like to be curious? Previous studies have demonstrated that we are particularly curious when uncertainty is high and when information provides us with a substantial update of what we know. It is unclear, however, whether this drive to seek information (curiosity) is appetitive or aversive. Curiosity might correspond to an appetitive drive elicited by the state of uncertainty, because we like that state, or rather it might correspond to an aversive drive to reduce the state of uncertainty, because we don’t like it. To investigate this, we obtained both subjective valence (happiness) and curiosity ratings from subjects who performed a lottery task that elicits uncertainty-dependent curiosity. We replicated a strong main effect of outcome uncertainty on curiosity: Curiosity increased with outcome uncertainty, irrespective of whether the outcome represented a monetary gain or loss. By contrast, happiness decreased with higher outcome uncertainty. This indicates that people were more curious, but less happy about lotteries with higher outcome uncertainty. These findings raise the hypothesis, to be tested in future work, that curiosity reflects an aversive drive to reduce the unpleasant state of uncertainty.